Ultrasonography: an aid in molecular subtyping of breast carcinoma - Thakur Shruti; Thakur Charu Smita; Thakur Vijay; Rana Nidhi; Jhobta Anupam; Kapila Sumala (Journal of Ultrasonography)
The recognition of molecular subtypes of breast cancer has initiated a new regimen of targeted therapy. Early diagnosis is a key step in improving survival. Therefore, a cost-effective and widely available imaging tool is needed for the timely detection and prediction of the molecular profile of breast cancer.